Growth Rate Analysis of Catfish from Cross Breeding of Sangkuriang, Masamo and Phyton Strains - Astuti, Ni Kadek Puji; Abidin, Zaenal; Nur’aeni Setyowati, Dewi (Jurnal Perikanan Unram, 2019)
The research aims to know the cross results of a better growth rate than the uncrossed missed. The cross is measured in units of weight (gram) and length (cm) of fish, Survival Rate (SR) and Feed Conversion Ratio (FCR). The design used in this study is the group Random Plan (RAK) with a replay of 3 times and analyzed using a print analysis of variance (ANOVA) at a real level of 0.05 with a confidence interval of 95%. Based on the results of the study gained that the results of the cruciation ? Sangkuriang >< ? Masamo has the highest growth value weighing 302, 0a g/tail and length 31, 2a cm/tail For 60 days of maintenance and Feed Conversion Ratio (FCR) is best of 0.9 different real (p < 0.05) Other uncrossed and missed results.